Digital infrastructure construction and the development of new-quality productive forces in enterprises - Zhixiong Yang; Jishun Zhang (Scientific Reports)
Abstract Digital infrastructure is the foundation for the development of digital technologies, providing the necessary production materials for the development of the digital economy and new types of productivity. This study aims to explore the impact of digital infrastructure construction on the new types of productivity of enterprises. Using the “Broadband China” demonstration cities as a quasi-natural experiment, empirical analysis is conducted based on data from A-share listed companies between 2011 and 2023, employing a difference-in-differences approach with multiple time points. The study finds that the “Broadband China” demonstration city pilot significantly promoted the improvement of enterprise new-type productivity, and this conclusion remains robust after several tests. Further analysis of the mechanism reveals that digital infrastructure promotes the development of new-type productivity by accelerating the smart transformation of enterprises, enhancing their level of informatization, and boosting innovation capabilities. Heterogeneity analysis shows that the policy has a more significant effect on improving the new-type productivity of enterprises in sub-provincial cities, private enterprises, and growth-stage enterprises. This research not only provides empirical evidence for the empowerment of enterprise new-type productivity development through digital infrastructure but also enriches the research on how macro policies influence micro-level enterprises. Furthermore, it provides theoretical references and practical guidance for the development of the digital economy and the acceleration of digital technology advancements in other Chinese cities and many developing countries.